Failure in rock with intersecting rough joints under uniaxial compression. (October 2021) - Liu, Xige; Zhu, Wancheng; Zhang, Penghai; Li, Lankun
Abstract: Uniaxial compressive tests were performed on Y-jointed granite specimens to explore how intersecting rough joints affect the strength, failure mode, and precursory damage characteristics of the jointed rock mass. The mechanical properties, joint dip angles, and joint roughness of the specimens were measured prior to the tests, then the loading stress, surface displacement fields, acoustic emission (AE) signals, and failure modes were recorded during the loading process. As the uniaxial compressive strength ( σ c ) of the specimens increased, three different failure modes appeared: shear failure along the persistent joint with rock wedge falling, compressive failure with rock wedge ejection, and overall crushing accompanied with rock fragment splashing, the σ c thresholds of the three failure modes are about 50 MPa and 90 MPa, respectively. The deformability of the specimens weakened gradually as σ c increased. AE events spread from the joint surface to the interior of the rock block until final failure. For specimens that failed in shear mode, multiple sudden stress drops along with sharp displacement increases occurred during the tests but no entire failure occurred. Other specimens tended to present one eventual unstable failure. When the peak shear strength of the non-persistent joint was higher than or near to that of the persistent joint, the σ c of a given Y-jointed specimen was mainly determined by the persistent joint. Otherwise, it was simultaneously controlled by the two joints. Both the joint dip angle and joint roughness were found to significantly influence the σ c of the specimens. Each stress drop was accompanied by significant AE signal variations, though the AE indicators are difficult to effectively utilize for early warning of specimen failure. Highlights: The effects of joint dip angle and joint roughness on the strength of Y-jointed granite specimens were investigated. Three different failure modes emerged as the peak compressive strength of the Y-jointed specimens increased. Shear failure is not the main failure mode in the jointed rock mass under high geo-stress. Unlike the damage location, the early warning time for specimen failure differs substantially in different cases.